Bellingham delegation, Alaska Yukon Pacific Exposition, Seattle, 1909. - Nowell, Frank H., 1864-1950 (1909)
On verso of image: Bellingham group Alfred C. Millican, laterhead of History Dept. at Ballard High School (1915-1922?) & subsequently Super. of Schools at Marysville, Wn (1922-9) and at Port Angeles, Wn. (1929-31) Linton P. Bennett, later principle of Ballard High School (1915-1923)& Broadview High (1923-[?]) Mr. Rhoades later head of Math dept. at Ballard High (1915-1940?) Juliet o'Hearn (?), English teacher at Queen Anne High & later at Ballard High School Miss Barrett Sewing teacher at Ballard High School To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number